The primary care toolkit : practical resources for the integrated behavioral care provider - James, Larry C. (2017)
Includes evidence-based practice guidelines, fact sheets, assessment inventories, and group protocols; thus, highly practical Addresses the major clinical problems and complaints encountered in primary care settings Written by leading experts in their fields